Distribution of neck circumference percentiles and their relationship with anthropometric measurements in children - Márquez Ibarra, Adriana Alejandra; Valbuena Gregorio, Edith; González Ponce, Ana Maria; Barrera Hernández, Laura Fernanda (Horizonte Sanitario, 2023)
Objective: To determine the relationship between neck circumference and anthropometric variables; to compare this circumference with percentile values proposed in 2021. Materials and methods: Cross-sectional, analytical study in a sample of 392 schoolchildren between 6 and 12 years of age, residents of Obregon City, Sonora, Mexico. Pearson correlations were performed; and the neck circumference data of 331 children were contrasted with the reference percentiles of a study carried out in central Mexico. Results: 44.64% were found to be normal weight, 14.29% underweight, 22.19% overweight and 18.88% obese. The mean neck circumference was 27.36±2.80 in girls and 28.44±2.78 in boys. In the subanalysis, neck circumference was higher in boy’s vs girls (28.04±2.62 vs 26.89±2.54). Twenty-one.91% of girls and 20.92% of boys were above the 97th percentile reference percentile, and at the 25th percentile was 19.66% of girls and 18.15% of boys. No girls were detected in the 3rd, 85th, 95th, and 97th percentiles; and in boys in the 3rd and 97th percentiles. Neck circumference was correlated with all anthropometric measurements (hip circumference, weight, waist circumference, BMI, CTI, and height). Conclusions: Neck circumference is related to BMI; therefore, it could be a secondary indicator of overweight or obesity. Keywords: Neck; Body Mass Index; Obesity; Children.